Estimating Mangrove Forest Health in the Bama Resort Area Baluran National Park, Situbondo, East Java - Chairul, Chairul; Jannah, Miftahul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Research on Estimating Mangrove Forest Health in the Bama Resort Area, Baluran National Park, Situbondo, East Java was conducted in 2 locations namely Pantai Bama and Tanjung Cemara from January to February 2024. The purpose of this study was to determine the vegetation structure and health of mangrove forests in the Bama Resort area. The method used in this study is the method of nested plots with transects with the number of plots used as many as 10 plots in each location. The research was conducted from January to February. Mangrove canopy cover data were taken using Monmang Vers 2.0 application with hemispherical photography method. The results showed that there were 8species of mangroves found. In the Bama Beach area, 3 species of true mangroves were found with the highest INP of the three levels found in R. apiculata and H 'classified as low category. While in Tanjung Cemara found 6 species of true mangroves and 1 asociate mangrove, with the highest INP of seedling and sapling levels found in R. apiculata and for tree levels found in R. Stylosa, with the value of H' classified as moderate category. Mangrove health conditions in the Bama Resort area are in moderate condition (55,683%).